Naskah Surat Tariqah: Kritik Tuanku Nan Garang Atas Sikap Anti Tarekat dan Anti Jihad Sayyid Uthman Al-Batawi - Muhamad Shoheh (Tsaqofah, 2017)
This article discusses the polemics that took place between two 19th-century clerics regarding tarekat and jihad against the Dutch colonial government. The cleric is Sayyid Uthma>n al-Batawi with Shaykh Isma'il Al-Minangkabau. The intended polemic is recorded in the classic Nusantara script entitled Surat T{ari>qah. The manuscript is a collection of the National Library of Indonesia with the code and number: 104a K.F.H 1/30. The text of Surat T{ari>qah is Dr. C. Snouck Hurgronje obtained from K.F. Holle. The manuscript was written by one of Shaykh Isma'il alMinagkabau disciples in order to defend the blasphemy, insults, and perversion of Sayid ‘Uthma> n. The text was then sent to Sayid 'Uthma>n and Snouck Hurgronje (close friend and protector of Sayid ‘Uthma>n). What are the contents of the manuscript? How was the defense that Ismael's disciples expressed against the insults and blasphemies of Sayid 'Uthma>n? This paper was made to answer the two problems.